Association of plasma trimethylamine N-oxide levels with atherosclerotic cardiovascular disease and factors of the metabolic syndrome. (October 2021) - Ringel, Clemens; Dittrich, Julia; Gaudl, Alexander; Schellong, Paul; Beuchel, Carl Friedrich; Baber, Ronny; Beutner, Frank; Teren, Andrej; Engel, Christoph; Wirkner, Kerstin; Thiele, Holger; Büttner, Petra; et al.
Abstract: Background and aims: The association of plasma trimethylamine N -oxide (TMAO) with atherosclerotic cardiovascular disease (ASCVD), diabetes mellitus (DM) and its determinants, as well as the role of TMAO as a predictor for short and long-term mortality, is still under discussion. We investigated associations between four plasma metabolites of the TMAO pathway and different clinical manifestations of atherosclerosis, diabetes determinants, and risk of short and long-term mortality in patients with stable ASCVD, acute myocardial infarction (AMI), cardiogenic shock (CS), and DM in three independent cohorts. Methods: TMAO and its dietary precursors were simultaneously quantified by liquid chromatography-tandem mass spectrometry in a total of 2655 participants of the German Leipzig Research Center for Civilization Diseases (LIFE)-Heart study, LIFE-Adult study, and the European Culprit Lesion Only PCI versus Multivessel PCI in Cardiogenic Shock (CULPRIT-SHOCK) multicenter trial. Associations with ASCVD manifestations, metabolic syndrome, 30-day mortality of patients with AMI and CS, and long-term mortality of subjects with suspected coronary artery disease (CAD) were analyzed. Results: TMAO plasma levels were not independently associated with stable ASCVD. Elevated TMAO plasma concentrations were independently associated with obesity (odds ratio, 1.23; p < 0.01) and DM (odds ratio, 1.37; p < 0.001) in LIFE-Heart. The latter association was confirmed in LIFE-Adult. We found no association of TMAO plasma levels with short-term mortality in patients with AMI and CS. However, TMAO plasma levels were independent predictors of long-term mortality in patients with suspected CAD (hazard ratio, 1.24; p < 0.05). Conclusions: Potential proatherogenic mechanisms of TMAO seem to have no short-term effect in AMI. Presented associations with diabetes mellitus and obesity suggest that TMAO might have a functional role in metabolic syndrome. Highlights: No association of trimethylamine N -oxide (TMAO) with atherosclerotic cardiovascular disease in a large, deeply-characterized cohort. TMAO is no independent predictor of short-term mortality in acute myocardial infarction with cardiogenic shock. Association of TMAO with diabetes mellitus in a cohort of the general population.